Breeding for the improvement of indigenous chickens in Bangladesh: performance of second generation - Faruque, Shakila; Bhuiyan, AKFH; Ali, Md Yousuf; Sarker, MSK; Joy, Ziaul Faruque (Asian Journal of Medical and Biological Research, 2017)
The improvement of productivity of indigenous chicken is a long desire in the country. Present research is a part of the long-term selection program being undertaken to evaluate the carcass characteristics and expected response to selection of second generation (G2) of indigenous chicken under intensive management in Bangladesh. A total of 1643-day-old chicks comprising of 3 types of chicken namely Naked Neck (NN), Hilly (H) and Non-descript Desi (ND) were hatched in a two batches for this study. In second generation (G2), selection was practiced at 3 (three) stages of birds life, firstly and secondly at 8 and at 16 weeks of age, selection was performed on the basis of breeding value for 8 and 16 week body weight. Thirdly, at 40-week of age, on the basis of an index comprising the parameters of age at sexual maturity (ASM), body weight (BW), egg production (EP) and egg weight (EW). Improvement target of egg weight was to increase by 1g and improvement target of egg production rate was to increase by 2 % per generation. The main target was the mean body weight in H, ND and NN chicken has to be gone up from the initial eight-week body weight of 375, 342 and 331g to 500 g at eight weeks of age. At 8, 10 and 12 weeks of age, six birds from each genotype were slaughtered to analyze the meat yield traits. Slaughter data were analyzed in a 3(genotype)×3(slaughter age) factorial arrangement in CRD by General Linear Model (GLM) Univariate Procedure in SPSS Computer Program. Genotype and slaughter age had significant effect (p<0.001) on dressing percentage. Body weight at 8 weeks of age was expected to improve by 51.21 vs. 24.03; 37.74 vs. 15.47 and 26.26 vs. 9.65g; respectively for ND, H and NN males and females. In terms of body weight H genotype was superior and NN genotype was for dressing percentage. As a result of selection; EP, BW increased and ASM reduced in second generation than that of the foundation stock. Asian J. Med. Biol. Res. March 2017, 3(1): 66-71